Nrdp1 Increases Ischemia Induced Primary Rat Cerebral Cortical Neurons and Pheochromocytoma Cells Apoptosis Via Downregulation of HIF-1α Protein - Zhang, Yuan; Yang, Ke; Wang, Ting; Li, Weiping; Jin, Xinchun; Liu, Wenlan (Frontiers in Cellular Neuroscience, 2017)
Neuregulin receptor degradation protein-1 (Nrdp1) is an E3 ubiquitin ligase that targets proteins for degradation and regulates cell growth, apoptosis and oxidative stress in various cell types. We have previously shown that Nrdp1 is implicated in ischemic cardiomyocyte death. In this study, we investigated the change of Nrdp1 expression in ischemic neurons and its role in ischemic neuronal injury. Primary rat cerebral cortical neurons and pheochromocytoma (PC12) cells were infected with adenoviral constructs expressing Nrdp1 gene or its siRNA before exposing to oxygen-glucose deprivation (OGD) treatment. Our data showed that Nrdp1 was upregulated in ischemic brain tissue at 3 h after middle cerebral artery occlusion and in OGD-treated neurons. Of note, Nrdp1 overexpression by Ad-Nrdp1 enhanced OGD-induced neuron apoptosis, while knockdown of Nrdp1 with siRNA attenuated this effect, implicating a role of Nrdp1 in ischemic neuron injury. Moreover, Nrdp1 upregulation is accompanied by increased protein ubiquitylation and decreased protein levels of USP8 in OGD-treated neurons, which led to a suppressed interaction between USP8 and HIF-1α and subsequently a reduction in HIF-1α protein accumulation in neurons under OGD conditions. In conclusion, our data support an important role of Nrdp1 upregulation in ischemic neuronal death, and suppressing the interaction between USP8 and HIF-1α and consequently the hypoxic adaptive response of neurons may account for this detrimental effect.